Work-Life Balance as a Mediator of Job Satisfaction among Indonesian Expatriates - Mandagi, Deske W.; Gerungan, Citra Adriana; Walean, Ronny H. (Jurnal Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: Expatriate job satisfaction has emerged as a critical topic in the context of increasing global workforce mobilities. This study aims to understand how lifestyle, job security, and work-life balance affect the job satisfaction of Indonesian expatriates living and working in Thailand. Methodology/approach: A quantitative research method was employed. A survey with structured questionnaires was administered to 200 Indonesian expatriates who had worked in Thailand for more than one year. The data were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software to examine the relationships between the factors. Results: The study found that lifestyle, job security, and work-life balance all have a positive and significant impact on job satisfaction. It also showed that work-life balance plays an important role in connecting lifestyle and job security to the overall job satisfaction. Conclusions: Non-financial factors such as a good lifestyle, feeling secure in one’s job, and having a balance between work and personal life are very important for Indonesian expatriates’ job satisfaction. Employers and decision-makers should seriously consider these factors. Limitations: The study only focused on Indonesian expatriates in Thailand who had worked there for more than a year; therefore, the results might not apply to all expatriates or other countries. Contribution: This study provides insights for employers, HR professionals, and policymakers in Indonesia on improving job satisfaction and reducing the need for skilled workers to move abroad. It adds to the fields of international human resource management and expatriate studies.